Rahnamūd́hā-yi maytūďk bih Shūrā́hā-yi Jabha-i Mill-i-i Pidar Vaṭan barā-yi sāzmāndahī-i faʼālīyat́hay-i tablīghī, tarvījī - Farīvar, Faridūn ("Shumārah-i musalsal 3.", 1980)
On the methodology for spreading the political ideology of the communist government among the people of Afghanistan.